Communication of nurses in childbirth care: the view of deaf women (Research, Society and Development, 2021)
This study aims to understand the perception of deaf women about communication with nurses in childbirth care. This is an descriptive, exploratory study with a qualitative approach, carried out with nine deaf women. Data collection was carried out in the period from September to October 2019, through semi-structured interviews in Brazilian Sign Language, with the participation of an interpreter. For data analysis, the thematic content analysis was used. Two categories emerged from the interviews: barriers to healthcare for deaf women and communication strategies for nurses during the delivery of deaf women. The perception of deaf women evidenced the existence of obstacles in the nurses' communication process during childbirth, caused by the lack of knowledge on the Brazilian Sign Language, the absence of an interpreter in the hospital environment, the companion as interlocutor in communication and the use of masks. In turn, in an attempt to communicate with the deaf user, the nurses used gestures, orofacial reading and writing in Portuguese; however, these strategies were quite limited and have not been effective in providing quality communication. There is an urgent need to value, use and disseminate Brazilian Sign Language in the training and professional qualification of nurses, in order to make the possibility of dialogue happen, without interference from third parties as interlocutors in communication, contributing to the development of an ethical and humanized care.